2009
DOI: 10.1007/s00134-009-1614-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ memory and psychological distress after ICU stay compared with expectations of the relatives

Abstract: Psychological distress symptoms were frequent among ICU survivors. Relatives expected the patients to be more distressed after ICU treatment than the patients reported. The strongest predictors of posttraumatic stress symptoms from the ICU were memoris about pain, lack of control and inability to express needs. Pessimism may be a reason for psychological distress and should be addressed during follow up, as pessimistic patients may need more motivation and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
3
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 37 publications
4
52
3
4
Order By: Relevance
“…Weinert and Sprenkle found that PTSD symptoms were highest in the groups with intermediate or fluctuating levels of wakefulness (sedation scores not provided) and lower for patients who were more consistently deeply sedated or completely alert and that the alert group was the least affected. A possible explanation for the relationship between alertness and PTSD symptoms in that study 20 and in the 4 studies I examined may be related to findings by Myhren et al 30 that "memory of pain, lack of control, and inability to express needs" were among the independent risk factors for PTSD. Similarly, in a qualitative study, Rattray et al 31 found that patients who were less aware of the surroundings or who had frightening experiences had more PTSD symptoms after discharge than did other patients.…”
Section: Discussionmentioning
confidence: 64%
“…Weinert and Sprenkle found that PTSD symptoms were highest in the groups with intermediate or fluctuating levels of wakefulness (sedation scores not provided) and lower for patients who were more consistently deeply sedated or completely alert and that the alert group was the least affected. A possible explanation for the relationship between alertness and PTSD symptoms in that study 20 and in the 4 studies I examined may be related to findings by Myhren et al 30 that "memory of pain, lack of control, and inability to express needs" were among the independent risk factors for PTSD. Similarly, in a qualitative study, Rattray et al 31 found that patients who were less aware of the surroundings or who had frightening experiences had more PTSD symptoms after discharge than did other patients.…”
Section: Discussionmentioning
confidence: 64%
“…Many who show distress will return quickly to normal function and some with a psychological disorder will follow a recovery trajectory [6]. Cross-sectional and cohort studies have reported anxiety and depression conditions in patients recovering from ICU admission at a higher rate than the general population, at between 24% and 45% at six weeks [7], three months [8] and one year [9]after ICU admission. Anxiety and depression conditions often co-exist with posttraumatic stress disorder (PTSD) [10].…”
Section: Recovery From Critical Illnessmentioning
confidence: 99%
“…In addition to anxiety, depression and PTSD, ICU survivors have often reported the absence of factual memory and the occurrence of delusional memories, including hallucinations or nightmares, throughout their recovery period [7]. ICU-related delusional memories are estimated to be present in around 30% to 70% of patients [10,12,13], are often persecutory in nature, and tend to be recalled with high vividness and in substantial detail [2].The direct cause of these delusional memories is unknown but is thought to be related to a combination of medication (including adrenaline, corticosteroids, opiates and sedative drugs such as propofol and benzodiazepine), sleep deprivation, and critical illness [12].…”
Section: Recovery From Critical Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta tendencia general de la familia a sobreestimar el malestar del paciente también se ha reflejado en otros estudios como por ejemplo el llevado a cabo por Myhren et al (2009) en Noruega con una muestra considerable de pacientes y de familiares tras el alta de UCI.…”
Section: Comparación Entre Pacientes Y Familiaresunclassified